Burden of tension-type headache in the Middle East and North Africa region, 1990-2019 - Saeid Safiri; Ali-Asghar Kolahi; Maryam Noori; Seyed Aria Nejadghaderi; Armin Aslani; Mark J. M. Sullman; Mehdi Farhoudi; Mostafa Araj-Khodaei; Gary S. Collins; Jay S. Kaufman; Kurosh Gharagozli (The Journal of Headache and Pain, 2022)
Abstract Introduction Tension-type headache (TTH) is the most prevalent neurological disorder. As there is a gap in the literature regarding the disease burden attributable to TTH in the Middle East and North Africa (MENA) region, the aim of the present study was to report the epidemiological indicators of TTH in MENA, from 1990 to 2019, by sex, age and socio-demographic index (SDI). Methods Publicly available data on the point prevalence, annual incidence and years lived with disability (YLDs) were retrieved from the global burden of disease (GBD) 2019 study for the 21 countries and territories in MENA, between 1990 and 2019. The results were presented with numbers and age-standardised rates per 100000 population, along with their corresponding 95% uncertainty intervals (UIs). Results In 2019, the age-standardised point prevalence and annual incidence rates for TTH in the MENA region were 24504.5 and 8680.1 per 100000, respectively, which represents a 2.0% and a 0.9% increase over 1990-2019, respectively. The age-standardised YLD rate of TTH in this region in 2019 was estimated to be 68.1 per 100000 population, which has increased 1.0% since 1990. Iran [29640.4] had the highest age-standardised point prevalence rate for TTH, while Turkey [21726.3] had the lowest. In 2019, the regional point prevalence of TTH was highest in the 35-39 and 70-74 age groups, for males and females, respectively. Furthermore, the number of prevalent cases was estimated to be highest in those aged 35-39 and 25-29 years, in both males and females, respectively. Moreover, the burden of TTH was not observed to have a clear association with SDI. Conclusions While the prevalence of TTH in the MENA region increased from 1990 to 2019, the incidence rate did not change. In addition, the burden of TTH in MENA was higher than at the global level for both sexes and all age groups. Therefore, prevention of TTH would help alleviate the attributable burden imposed on the hundreds of millions of people suffering from TTH around the region.